Phase I Study of Concomitant Pemetrexed and Cisplatin Plus External Beam Radiation Therapy in Patients with Locally Advanced or Metastatic Esophageal or Gastroesophageal Junction Carcinomas. (7th February 2016) - Elquza, Emad; Babiker, Hani M.; Howell, Krisha J.; Kovoor, Andrew I.; Brown, Thomas David; Patel, Hitendra; Malangone, Steven A.; Borad, Mitesh J.; Dragovich, Tomislav
ABSTRACT: Purpose : To establish the maximum tolerated dose (MTD) and safety profile of bi-weekly Pemetrexed (PEM) when combined with weekly cisplatin (CDDP) and standard dose external beam radiation (EBRT) in patients with locally advanced or metastatic esophageal and gastroesophageal junction (GEJ) carcinomas. Methods : We conducted an open label, single institution, phase I dose escalation study designed to evaluate up to 15–35 patients with advanced or metastatic esophageal and GEJ carcinomas. Results : 10 patients were treated with bi-weekly PEM, weekly CDDP, and EBRT. The MTD of bi-weekly PEM was determined to be 500 mg/m 2 .